Chemokine CX3CL1 has potential anti-fibrosis effect in mouse liver fibrosis - CHENG Qi, LI Ning, YU Kangkang, SHI Guangfeng (Jichu yixue yu linchuang, 2023)
Objective To explore the effect and mechanism of chemokine CX3CL1 on mouse liver fibrosis model. Methods C57BL/6 mice were randomly divided into CCl-4 model group and normal control group with 8 animals in each group. The model group was injected with 10% CCl-4 intra peritoneally for 6 weeks. After 6 weeks, the mice were sacrificed, and the pathological changes of the mouse liver were observed by HE staining. The level of CX3CL1 in peripheral blood of the mice was measured, and the expression level of CX3CL1 mRNA in the liver tissue of the mice was detected. In addition, in order to explore the mechanism of CX3CL1, the level of IFN-γ in mouse serum was detected as well. Results After the 6-week modeling, the liver pathology microscopy showed a successful modeling of liver fibrosis. The serum CX3CL1 level and liver tissue CX3CL1 expression in the model group were found to be significantly up-regulated, which suggested a potential impact on the pathogenesis of liver fibrosis. In addition, the level of IFN-γ in the serum of mice in the model group increased significantly. Conclusions CX3CL1 is related to liver fibrosis in mice, and its mechanism might be explained by promoting the production of IFN-γ so to prevent liver fibrosis.